The Analysis of the Mental Health of the Elderly After Retirement - Raini Retno Wulansari; Suwarjo Suwarjo (Postgraduate, University of Mataram, 2023)
Aging is an inevitable part of all individuals journeys. Many of these elderly people experience problems, especially elderly people who previously spent time working. In fact, there are many cases among the elderly who experience problems, especially for the elderly in the Purbalingga area, there are elderly people who fall ill due to economic problems and social changes that put pressure on the elderly after retirement, making them psychologically weakened. The aim of this research is to identify the mental health of the elderly after retirement. This research uses a qualitative case study approach. The data analysis technique used is triangulation techniques carried out using interviews, observation and documentation using the Miles and Huberman model. The results of this research found that cases of mental health in the elderly after retirement felt pressure due to the absence of strong social relationships between family and retirees and co-workers. So the feeling of loneliness, not being recognized, and the readiness to live a life of economic problems, and the feeling of anxiety during retirement have not been prepared. This has an impact on weakening the welfare and meaning of life of the elderly after retirement.